COMPARATIVE REFLECTIONS ON THE VINDICATION OF RIGHTS IN BRAZIL - Oquendo, Ángel (Revista Eletrônica de Direito Processual, 2021)
The present work examines the contrast between the vindication of rights in Brazil and the other countries in the Americas, especially with regard to the writ of security and analogous devices. It scrutinizes the historical development, along with points of convergence and divergence. Furthermore, the discussion contemplates legislation, doctrine, and the caselaw. Thereby, it purports to analyze admissibility, meritoriousness, appealability, preclusion, stare decisis, and the requirement of state action.